2016
DOI: 10.1108/mrr-11-2015-0268
|View full text |Cite
|
Sign up to set email alerts
|

The significance of perceived social-organization climate for creating employees’ innovativeness

Abstract: Purpose – The purpose of this study is to describe and explain the relationship between perceived social-organizational climate (PSOC), organizational citizenship behaviors (OCB) of other employees and innovative workplace behaviors (IWB) initiated and performed by employees. The mediating role of person-organization fit (P-O Fit) is tested within the relationship of PSOC, OCB and IWB. Design/methodology/approach – The study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 93 publications
0
27
0
Order By: Relevance
“…In the meantime, China is in a transitional state, which requires public organisations to respond swiftly and creatively to social problems and public demands. Change-oriented organisational citizenship behaviours are the key to meet this requirement (Turnipseed & Turnipseed, 2013;Wojtczuk-Turek & Turek, 2016). Public organisations could rely more on their younger employees, because their emphasis on agentic values is an antecedent to those behaviours (Arthaud-Day, Rode, & Turnley, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, China is in a transitional state, which requires public organisations to respond swiftly and creatively to social problems and public demands. Change-oriented organisational citizenship behaviours are the key to meet this requirement (Turnipseed & Turnipseed, 2013;Wojtczuk-Turek & Turek, 2016). Public organisations could rely more on their younger employees, because their emphasis on agentic values is an antecedent to those behaviours (Arthaud-Day, Rode, & Turnley, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have analyzed how POF affects IWB, also with contradictory results. Huang et al (2005) and Jin et al (2016) stated that there was no significant effect, while Afsar et al (2018) and Wojtczuk-Turek and Turek (2016) found that POF significantly influences IWB. The difference in these results suggests a research gap regarding the effect of POF on IWB.…”
Section: Introductionmentioning
confidence: 99%
“…Sobel's test results prove that innovative work behavior is able to mediate the influence of Person-job fit, Person organization fit, Person group fit has been identified by researchers as important factors affecting IWB (Afsar et al 2015, Saraç et al 2014, Wojtczuk-Turek and Turek 2016. Furthermore IWB is also significant with performance (De Jong and Den Hartog 2010, Pieterse et al 2010).…”
Section: Sobel Testsmentioning
confidence: 86%
“…Employee recruitment that places more emphasis on the suitability of the mission and personal values with organizational values makes the organization not only provide opportunities for employees to work, but also to encourage them to commit to the organization, perform well and be satisfied in their work (Tsai and Yen 2017). The study of Afsar et al (2015) also explained the organization fit can enhance the behavior of knowledge sharing which is expected to be able to encourage innovative work behavior of employees (Afsar et al 2015, Saraç et al 2014, Wojtczuk-Turek and Turek 2016. The third hypothesis testing shows that Person-Group fit has a positive impact on the Innovative Work Behavior (CR = 2.577; p = .010 < .005), with a significance level of 5%.…”
Section: Goodness Of Fit Testingmentioning
confidence: 99%